Diagnostic Accuracy of Flourodeoxyglucose-18 Positron Emission Computed Tomography in the Evaluation of Recurrent Papillary Thyroid Carcinoma with Patients’ Raised Thyroglobulin Level in Lahore - Shah, Loqman; Ansari, Fahmida; Ahmad, Munir; Younis, Muhammad Numair; Ali, Zarnab (Indus Journal of Bioscience Research, 2025)
Papillary thyroid carcinoma (PTC) is the most common type of thyroid cancer, typically associated with good prognosis and high survival rates if diagnosed on time. However, recurrence occurs in approximately 20-30% of cases, most often presenting as loco regional disease in the thyroid bed or cervical lymph nodes. Symptoms of recurrence may include a palpable neck mass, hoarseness caused by laryngeal nerve palsy or other causes. Dysphagia or cervical discomfort are not specific symptoms and many cases remain asymptomatic and are detected through surveillance. Risk factors for recurrence include lymph node metastasis, extra thyroidal extension, and aggressive histological variants. Detection involves serum thyroglobulin levels, and imaging studies. Several biomarkers like HBME-1, cytokeratin 19 (CK19), and ret oncogene have been proposed to aid in diagnosis of thyroid cancers. Objective: To determine the diagnostic accuracy of fluorodeoxyglucose-18 Positron Emission Tomography (FDG-18-PET) in the evaluation of recurrent papillary thyroid carcinoma in patients with raised serum thyroglobulin levels. Methods: A cross-sectional analytical study was conducted at Institute of Nuclear Medicine and Oncology (INMOL), Hospital, Lahore, Pakistan. 39 patients aged 25-77 years (mean age: 50.08) with raised serum thyroglobulin levels, and a history of papillary thyroid carcinoma suspicious of recurrence were included in the study using convenience sampling. Data was analyzed using SPSS version 26. Each patient underwent 18-FDG-PET/CT and tissue biopsy for histopathological correlation afterwards. Diagnostic Odds Ratio (DOR) was used to determine statistical significance. Results: Out of 39 patients, 18-FDG-PET/CT was able to correctly detect the recurrence in 26 patients. It missed 10 with papillary thyroid carcinoma and falsely diagnosed 1 patient which was found to have no recurrence on histopathological correlation and the 2 patients was PET-CT negative. 18-FDG-PET/CT demonstrated a sensitivity of 77.8%, and a specificity of 66.66%, indicating its moderate ability to correctly identify both true positives and true negatives. The overall diagnostic accuracy was 76.9%. Notably, the positive predictive value (PPV) was high at 96.6%, signifying that a positive 18-FDG-PET/CT result strongly suggests recurrence. Conversely, the negative predictive value (NPV) was low at 20.0%, revealing that negative result was unreliable, with a considerable number of false negatives (8 out of 10 PET-negative cases were positive upon histopathological correlation). The diagnostic odds ratio (DOR) of 7.0 reflects a moderate discriminative capacity of the test. Conclusion: The study concludes that FDG PET/CT demonstrates high positive predictive power and moderate diagnostic accuracy in detecting recurrent papillary thyroid carcinoma among patients with elevated serum thyroglobulin levels, though moderate sensitivity and lower negative predictive value highlights the risk of false negatives. Therefore, PET/CT should be interpreted in conjunction with clinical, biochemical, and histopathological data.